Integrating multi-criteria analysis with PDCA cycle for sustainable energy planning in Africa: Application to hybrid mini-grid system in Cameroon. (February 2020) - Nsafon, Benyoh Emmanuel Kigha; Butu, Hemen Mark; Owolabi, Abdulhameed Babatunde; Roh, Jong Wook; Suh, Dongjun; Huh, Jeung-Soo
Abstract: Rural communities in Africa are often poorly electrified and rely on polluting fuels for energy. Apart from the attendant health effects and greenhouse gas emissions from these energy sources, these systems are unreliable and more costly especially in long term use. Proposing a renewable energy installation plan for these communities often creates conflicting scenarios; requiring prioritization and opportunity cost. An improved MCDM method is an ideal approach that can solve this problem properly. This paper thus proposes a hybrid model that is based on integrating AHP-VIKOR with the PDCA cycle, for continuous improvement of the planning process. AHP and VIKOR were utilized for multi-criteria ranking to determine the optimal hybrid technology combination. The uniqueness of this model is the management support characteristic of the PDCA cycle that provides coherence between the planning process and the actual project, as well as criticisms and responses for the proposed system. The results show that the selected hybrid energy system does not only guarantee a reliable system configuration with unmet load of 2.45 kWh/year, it also has economic benefits over the least cost system and a standard diesel generator system respectively: income from power sales of 3, 816.7$/year and 745.11$/year; and savings from carbon pricing of 68, 810.17$/year and 8, 323, 774.7$/year.